Congenital Long QT Syndrome in Children and Adolescents: A General Overview - Elia Balestra; Marco Bobbo; Marco Cittar; Daniela Chicco; Biancamaria D'Agata Mottolese; Egidio Barbi; Thomas Caiffa (MDPI AG, 2024)
Congenital long QT syndrome (LQTS) represents a disorder of myocardial repolarization characterized by a prolongation of QTc interval on ECG, which can degenerate into fast polymorphic ventricular arrhythmias. The typical symptoms of LQTS are syncope and palpitations, mainly triggered by adrenergic stimuli, but it can also manifest with cardiac arrest. At least 17 genotypes have been associated with LQTS, with a specific genotype-phenotype relationship described for the three most common subtypes (LQTS1, -2, and -3). β-Blockers are the first-line therapy for LQTS, even if the choice of the appropriate patients needing to be treated may be challenging. In specific cases, interventional measures, such as an implantable cardioverter-defibrillator (ICD) or left cardiac sympathetic denervation (LCSD), are useful. The aim of this review is to highlight the current state-of-the-art knowledge on LQTS, providing an updated picture of possible diagnostic algorithms and therapeutic management.